Magic Card 3D Berbantuan Assemblr Edu Berbasis SETS Materi Gaya Meningkatkan Literasi Sains Kelas IV SDN Sumberjo 01 Kabupaten Blitar - Yuniasari, Mega Elvi; Fatih, Mohamad; Alfi, Cindya (Literasi: Jurnal Ilmu Pendidikan, 2024)
Science and technology learning has a role in realizing students' curiosity to understand how the universe works and interacts with human life on earth. However, there are still many students who find learning IPAS difficult, because of different student understandings. In addition, the use of learning media is urgently needed to support learning success. The purpose of this research is to develop Magic Card 3D media assisted by Assemblr Edu and to improve students' science literacy by using the media that has been developed. This study used the development procedure in the following research research and Development (R&D) steps with the Borg and Gall model. The method used is the Quasi Experiment, which is research that aims to determine the effect of treatment on others under controlled conditions. The subject of this study was a grade IV student of SDN Sumberjo 01 Blitar Regency. The number of students in one class consists of 20 students, and during the learning process will be divided into 2 large groups. The first group, the experimental group that will receive special treatment, namely during learning will use media. The next group is the conventional group, this group does not receive special treatment because they do not use learning media in learning. Researchers use this method, to determine the influence of the difference in learning using and not using media, as well as to measure the improvement of students' science literacy.  Keywords: Magic Card 3D, Assemblr Edu, SETS, Science Literacy